2022
DOI: 10.1007/s00068-022-02070-2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic cholecystectomy offers best outcomes following ERCP clearance of common bile duct stones: a meta-analysis

Abstract: Background Symptomatic calculus biliary disease is common with associated morbidity and occasional mortality, further confounded when there is concomitant common bile duct (CBD) stones. Choledocholithiasis and clearance of the duct reduces recurrent cholangitis, but the question is whether after clearance of the CBD if there is a need to perform a cholecystectomy. This meta-analysis evaluated outcomes in patients undergoing ERCP with or without sphincterotomy to determine if cholecystectomy post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“… 17 Surprisingly, we found that having undergone cholecystectomy (either before or after ERCP) increased the risk of developing long-term benign complications. These findings contrast with what has been reported in other studies, 18 where post-ERCP cholecystectomy is associated with an overall decrease in biliopancreatic complications following ERCP.…”
Section: Discussioncontrasting
confidence: 99%
“… 17 Surprisingly, we found that having undergone cholecystectomy (either before or after ERCP) increased the risk of developing long-term benign complications. These findings contrast with what has been reported in other studies, 18 where post-ERCP cholecystectomy is associated with an overall decrease in biliopancreatic complications following ERCP.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent meta-analysis showed that prophylactic cholecystectomy after ERCP- endoscopic sphincterotomy (ERCP-ES) CBD stone clearance was better than the wait-and-see policy. It was associated with fewer complications (acute cholecystitis, acute cholangitis, acute pancreatitis and biliary colic)[ 12 ]. However, it should be particularly considered in extremely elderly patients with limited life expectancy or unfit frail patients.…”
Section: Introductionmentioning
confidence: 99%